Public spending reallocations and economic growth across different income levels - Acosta-Ormaechea, Santiago; Morozumi, Atsuyoshi (Wiley, 2017)
This paper examines the effects of public spending reallocations on economic growth. Assembling a disaggregated public spending dataset of 83 countries over the 1970-2011 period, we show that spending reallocations towards education, from health and social protection, have significant growth-promoting effects across a wide range of countries' income levels. However, income heterogeneity matters, particularly when reallocations involve infrastructure spending. Specifically, a reallocation from this spending to education also promotes growth, albeit primarily when the income level is low. This occurs because the effects of infrastructure spending are particularly weak in low-income countries, possibly due to the low quality of governance.